Ethical Issues in SARS Control - Sabine Schipf (2007)
In November 2002, severe acute respiratory syndrome (SARS) emerged in China and spread rapidly around the globe. The pathogen was unknown, and no vaccine or effective therapy was available. The initial steps taken to cope with SARS on the international, national and local level were made in uncertainty and without scientific knowledge. SARS is a reminder of the infectious diseases which continually threaten the public. The society reacted with fear and panic. Besides social disruption and economic losses, political response to infectious diseases posed ethical conflicts. The central conflict was protection of the public good versus protection of individual rights. SARS was already contained, the ethical issues persisted. This diploma thesis provides an insight into this topic. The thesis is divided into two sections. The first section provides background information and the second is the manuscript of an article. The subject of the background information is infectious diseases; the relationships among ethics, public health and politics; professional codes of ethics provided for health care workers (HCWs), information on the evolution of public health ethics, and the development of the SARS epidemic in association with ethical conflicts.